INFLUENCE OF PRO-INFLAMMATORY ADIPOKINES IN THE VASCULAR PHENOTYPE OF OVERWEIGHT AND OBESE ADOLESCENTS. (June 2022) - De Blas, Ana; Álvarez-Pitti, Julio; Torro, Maribel; Aguilar, Francisco; Ponce, Francisco; Lurbe, Empar
Abstract : Objective: Obesity is a complex disease that leads to an adipocyte dysfunction favoring a profile characterized by insulin and leptin resistance with low adiponectin values. The objective of the present study is to assess in overweight and obese subjects the impact of the unfavorable profile of adipokines in blood pressure and vascular function. Design and method: Overweight and obese adolescents referred for cardiovascular risk assessment were included in a cross-sectional study. Height, body weight, and body composition were measured by bioelectrical impedance analysis. Hemodynamics were assessed by office blood pressure. Pulse wave velocity (PWV) and central blood pressure (cBP) were measured with Sphigmocorâ device. The logarithm of Aortic pulse pressure (AoPP) was calculated. Metabolic profile including fasting glucose and insulin levels, lipids profile and uric acid was assessed. Leptin and adiponectin were measured and the leptin/adiponectin ratio (L/A r) was calculated. Results: A total of 60 subjects (mean age 12.5 years, 53% male, and 68% obese) were included. Participants with obesity (mean BMI Z-score 2, 3 ± 0.2) had higher levels of daytime SBP (118 Vs 116 mmHg; p = 0.05), and no differences in PWV (5.5 vs 5 m/s; p = 0.06) as compared to overweight. No differences were found in the metabolic profile, in contrast, leptin, was higher in subjects with obesity (43 vs 30 ng/L p = 0.045). Overall, a positive and significant correlation was found between leptin and PWV. Focusing on cBP values, a significant and negative correlation among adiponectin and AoPP was observed. In contrast a positive correlation to L/A r was found (figure). The multiple regression analysis showed that PWV was partially explained by L/A r and AoPP by adiponectin, when age, sex, BMI Zscore, insulin, leptin, and L/A r were included in the model. Conclusions: Obesity leads to an adipokines profile that is related to unfavorable vascular phenotypes in youth.